PROSES ADAPTASI KEMBALI PASCA KONFLIK DISKRIMINASI ETNIS PAPUA DI KOTA SEMARANG - Diva Sinar Rembulan; Turnomo Rahardjo; Hapsari Dwiningtyas Sulistyani (Interaksi Online, 2022)
Phenomenon of multicultural society in Indonesia should not be a barrier for people to live in harmony. However, in reality, the cultural differences often causes conflict, especially among minorities, one of them is Papuan ethnic who experience discrimination. Then, it becomes a new problem how they return to live with the society after the conflict happened. This study uses a qualitative method, with an interpretive paradigm and a phenomenological approach. The data collected with in-depth interview technique. The theories used in this study are acculturation process theory, integrative theory of cross-cultural adaptation and face negotiation theory. The results of this study reveal that, (1) the process of re-adaptation is a dynamic process of stress-adaptation that related to the previous communication to encourage individual to take certain communication actions at the next phase. (2) this process occurs through three phases, the recovery phase, the initiation of communication phase and the assimilation phase. The recovery phase is an individual’s effort to prepare and reduce post-conflict stress before returning to society. The initiation of communication phase is an individual’s effort to open communication acess opportunities with the society and The final phase is assimilation phase is an individual’s attempt to balance their identity by collaborating their old culture with the new culture through communication strategies. (3) the process of re-adaptation doesn’t always run smoothly due to communication barrier, there are post-conflict stereotypes and affected by other conflict. (4) There are the different of communication strategies between individual who live alone and live in a group. For individual who live alone or self-concerned, the communication strategies carried out by starting to use Javanese and being friendly. Meanwhile, individual who live in a group or mutual-concern have more responsibility for their fellow members, manage the group structure, repair group facilities, build and maintain communication between group members and the society. This communication strategy resulted a better relationship stage before the conflict happened.